Tissue-Specific Effects of Bariatric Surgery Including Mitochondrial Function - Simon N. Dankel; Vidar Staalesen; Bodil Bjørndal; Rolf K. Berge; Gunnar Mellgren; Lena Burri (Hindawi Limited, 2011)
A better understanding of the molecular links between obesity and disease is potentially of great benefit for society. In this paper we discuss proposed mechanisms whereby bariatric surgery improves metabolic health, including acute effects on glucose metabolism and long-term effects on metabolic tissues (adipose tissue, skeletal muscle, and liver) and mitochondrial function. More short-term randomized controlled trials should be performed that include simultaneous measurement of metabolic parameters in different tissues, such as tissue gene expression, protein profile, and lipid content. By directly comparing different surgical procedures using a wider array of metabolic parameters, one may further unravel the mechanisms of aberrant metabolic regulation in obesity and related disorders.